In vivo kinetics of U4/U6·U5 tri-snRNP formation in Cajal bodies - Novotný, Ivan; Blažíková, Michaela; Staněk, David; Herman, Petr; Malinsky, Jan (Molecular biology of the cell, 2011)
The U4/U6·U5 tri-small nuclear ribonucleoprotein particle (tri-snRNP) is an essential pre-mRNA splicing factor, which is assembled in a stepwise manner before each round of splicing. It was previously shown that the tri-snRNP is formed in Cajal bodies (CBs), but little is known about the dynamics of this process. Here we created a mathematical model of tri-snRNP assembly in CBs and used it to fit kinetics of individual snRNPs monitored by fluorescence recovery after photobleaching. A global fitting of all kinetic data determined key reaction constants of tri-snRNP assembly. Our model predicts that the rates of di-snRNP and tri-snRNP assemblies are similar and that ∼230 tri-snRNPs are assembled in one CB per minute. Our analysis further indicates that tri-snRNP assembly is approximately 10-fold faster in CBs than in the surrounding nucleoplasm, which is fully consistent with the importance of CBs for snRNP formation in rapidly developing biological systems. Finally, the model predicted binding between SART3 and a CB component. We tested this prediction by Förster resonance energy transfer and revealed an interaction between SART3 and coilin in CBs.
Keywords: antigeny nádorové; spliceozomy; RNA Precursors; Models, Molecular; Ribonucleoprotein, U5 Small Nuclear; HeLa buňky; Spliceosomes; ribonukleoproteiny malé jaderné; RNA Splicing; proteiny vázající RNA; vazba proteinů; HeLa Cells; Humans; kinetika; sestřih RNA; Ribonucleoproteins, Small Nuclear; Coiled Bodies; Kinetics; prekurzory RNA; RNA-Binding Proteins; buněčné jádro; Cell Nucleus; malý jaderný ribonukleoprotein U4-U6; Cajalova tělíska; Antigens, Neoplasm; RNA Helicases; malý jaderný ribonukleoprotein U5; Cell Line, Tumor; nádorové buněčné linie; jaderné proteiny; Nuclear Proteins; lidé; molekulární modely; Ribonucleoprotein, U4-U6 Small Nuclear; Protein Binding; RNA-helikasy